An engineered adipose formulation decreases hepatic inflammation and fibrosis in a rodent model of metabolic dysfunction-associated steatotic liver disease - Choi, Youngshim; Ma, Yinyan; Tom, Samson; Danilkovitch, Alla; Yu, Liqing (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionMetabolic dysfunction-associated steatotic liver disease (MASLD) and its progressive stage metabolic dysfunction-associated steatohepatitis (MASH) represent a leading cause of liver-related morbidity and mortality in the U.S. and worldwide. Given the high prevalence and rapid growth of MASLD, the economic and health burden, and MASH-associated morbidity and mortality, there is an unmet medical need for therapies that can stop, slow, or reverse the progression of MASLD. Adipose tissue plays a key role in metabolic health and MASLD pathogenesis through its regulation of energy metabolism and endocrine function. Metabolic dysfunction is often associated with a chronic state of low-grade inflammation in the body including adipose tissue.MethodsIn this study, we tested an engineered adipose formulation (AF) composed of a combination of culture-expanded adipose stromal vascular fraction (SVF) cells and adipose tissue particulates in the treatment of MASLD. Human, rat, and mouse AFs (hAF, rAF, and mAF) showed anti-inflammatory activity, which was mediated predominantly by soluble factors present in the adipose particulate. In vivo effects of AFs were evaluated in two rodent models of MASLD: i) obese Zucker rats fed a high-fat, high-cholesterol, and high-fructose diet that mainly manifest hepatic steatosis; and ii) liver-specific CGI-58 knockout mice (LivKO) on a Western diet that display MASH pathologies.ResultsSubcutaneous implantation of hAF and rAF in obese Zucker rats significantly reduced hepatic triglycerides. In LivKO mice, mAF reduced hepatic inflammation and fibrosis, though not steatosis, as evidenced by significant decreases in hepatic M1 macrophages and mRNAs for proinflammatory and fibrogenic genes. Immunogenicity testing demonstrated that allogeneic rAF did not induce an immune response, whereas, as anticipated, xenogeneic hAF in rats triggered anti-hAF antibody formation. Despite an immune response against xenogeneic hAF, treatment of rats with hAF ameliorated hepatic steatosis.DiscussionAF has the potential to treat MASH. Future studies focused on the optimization of AF composition, optimal dose and treatment regimen are warranted.